Transformasi Kepemimpinan dengan AI: Peluang dan Risiko bagi Dunia Kerja Masa Kini - Fanny Ariza Afifa; Avanin Hanina Sukotjo; Ahmad Yusril Ghufron; Mochammad Isa Anshori (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2026)
The digital transformation driven by the acceleration of Artificial Intelligence (AI) has fundamentally transformed leadership paradigms and the structure of the modern workplace. This study aims to provide an in-depth analysis of the various strategic opportunities and systemic risks arising from the integration of AI into contemporary organizational leadership practices, where technology is no longer merely a tool but a collaborative partner in managerial processes. Using a Systematic Literature Review (SLR) method on 30 reputable scientific journals with publications spanning up to 2026, this article analyzes the transition of the leader’s role from a conventional hierarchical model toward the concept of Augmented Leadership. Data analysis results indicate that AI implementation offers significant opportunities through data-driven decision-making systems with high precision, intelligent resource allocation optimization, and enhanced leadership intervention effectiveness, which has been documented to reach up to 35%. However, this transformation also brings a series of complex multidimensional risks, including algorithmic biases that could trigger inequality cascades, ethical dilemmas related to operational transparency (black box), and the potential erosion of the meaning of work for employees. The discussion in this article emphasizes that the success of this transformation depends not only on technical expertise, but also on redefining leadership competencies to prioritize emotional intelligence and ethical governance frameworks such as the CARE Framework (Control, Awareness, Responsibility, and Evaluation).